2022
DOI: 10.1038/s41598-022-24588-6
|View full text |Cite
|
Sign up to set email alerts
|

Model experiments on hydraulic properties around multiple piers with reproduced 3D geometries

Abstract: The effects of multiple piers with 3D geometries on water levels during floods, as well as riverbed fluctuations and local scour after floods were examined via hydraulic model experiments. The Kintaikyo Bridge in Japan, a world-famous historical triple-wooden-arch bridge, was modeled at a scale of approximately 1/276. The number of model piers was set to four, as in the real bridge, and they were 3D printed and installed in the sand layer of an open channel. To provide adequate information on the pier installa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
0
0
Order By: Relevance
“…Previous research has shown that flow velocity, water depth, and geometric characteristics of structures significantly impact the development of riverbed scour 62 . Therefore, this study focuses on double-column shallow foundation bridges and investigates the variation in scour depth around the foundation under different fluid elevations and inflow velocities over time.…”
Section: Impact Of Different Water Depths and Flow Velocities On The ...mentioning
confidence: 99%
“…Previous research has shown that flow velocity, water depth, and geometric characteristics of structures significantly impact the development of riverbed scour 62 . Therefore, this study focuses on double-column shallow foundation bridges and investigates the variation in scour depth around the foundation under different fluid elevations and inflow velocities over time.…”
Section: Impact Of Different Water Depths and Flow Velocities On The ...mentioning
confidence: 99%